Pengaruh Disiplin Belajar dan Variasi Mengajar Guru Terhadap Prestasi Belajar Siswa pada Mata Pelajaran Ekonomi Kelas XA MA NW Palapa Nusantara - Irwan Yon Hadi (Pendidikan Al-Gafari, 2023)
Problem education The same very No Can separated from life human. Education for life man is life absolute must fulfilled throughout life. Without an Education group man will difficult For life develop in line with his goals For forward. Study This For know influence discipline study and variety teach teachers against performance Study eye student lesson economics in students class XA MA NW Palapa Nusantara. Type research used is descriptive quantitative. Population and sample in study This is whole student class XA MA NW Palapa Nusantara. Data collection using questionnaire and documentation. Collected data analyzed with technique descriptive and technical regression. Based on t count results obtained t value count of 2.013 more big from t table of 1.699 with mark probability 0.009<0.05, which means hypothesis beeps There is influence discipline Study to performance eye study lesson economy accepted. And based on hypothesis testing with using the t test, the results obtained that mark tcount of 2,383 more big from t table = 1.699, with mark significance 0.005<0.05, which means hypothesis that reads There is influence variation teach teachers against performance eye study lesson economy accepted. kindly simultaneous Based on results data analysis that discipline study and variety teaching influential teachers to performance Study economy of 50.5% where Fcount = 4.073 more large and F table = 3.35 so that Ha is accepted With thereby can pulled conclusion that there is significant influence between discipline study and variety teach teachers against performance Study eye student lesson the economy at MA NW Palapa Nusantara is good in a manner Partial nor simultaneous.